Prisoners of the empire : inside Japanese POW camps - Kovner, Sarah (Sarah C.), 1973- (Harvard University Press, 2020)
"In just five months, from the airstrikes on Pearl Harbor to the fall of Corregidor, the Empire of Japan took prisoner more than 140,000 Allied servicemen and 130,000 civilians from a dozen different countries. In the ensuing chaos, all of them had to find a way to live -- or die -- in hundreds of camps spread across thousands of miles, from Manchuria to Manila, from Singapore to Nagasaki. Forty percent of American servicemen did not survive, and more Australians died in captivity than were killed in combat. Based on archives and interviews in eight countries and five languages, Prisoners of the Empire shows not just how POWs survived, but why they had to endure such a terrible ordeal"--